Mild small-for-gestational-age as a non-negligible risk factor for short stature. (January 2023) - Higuchi, Ryunosuke; Koga, Hiroshi; Sugino, Noriko; Bonno, Motoki; ,
Abstract: Risk of subsequent short stature remains unclear among mild small-for-gestational-age (SGA) infants with birthweight <10th percentile and ≥−2 standard deviations. In this multicenter cohort study in Japan, height was found to be <−2 standard deviations at 3 years old even in 18 % of mild-SGA infants. Highlights: Mild small-for-gestational-age (SGA) infants are commonly not indicated for growth hormone therapy. The incidence of short stature or non-catch-up growth has not been well studied in this population. Even among mild-SGA infants, short stature at 3 years of age was observed in 18 %. Our findings provide basic data on the development of mild-SGA infants and risk factors for subsequent short stature.